Multidimensional Proteomic Approach of Endothelial Progenitors Demonstrate Expression of KDR Restricted to CD19 Cells - Guerin, Coralie L.; Guyonnet, Léa; Goudot, Guillaume; Revets, Dominique; Konstantinou, Maria; Chipont, Anna; Chocron, Richard; Blandinieres, Adeline; Khider, Lina; Rancic, Jeanne; Peronino, Christophe; Debuc, Benjamin; et al. (Stem cell reviews and reports, 2021)
Endothelial progenitor cells (EPCs) are involved in vasculogenesis and cardiovascular diseases. However, the phenotype of circulating EPCs remains elusive but they are more often described as CD34 + KDR + . The aim of the study was to extensively characterize circulating potential vasculogenic stem cell candidates in two populations of patients with cardiovascular disease by powerful multidimensional single cell complementary cytometric approaches (mass, imaging and flow). We identified cellular candidates in one patient before and after bioprosthetic total artificial heart implantation and results were confirmed in healthy peripheral and cord blood by mass cytometry. We also quantified cellular candidates in 10 patients with different COVID-19 severity. Both C-TAH implantation and COVID-19 at critical stage induce a redistribution of circulating CD34 + and CD19 + sub-populations in peripheral blood. After C-TAH implantation, circulating CD34 + progenitor cells expressed c-Kit stem marker while specific subsets CD34 + CD133 −/+ CD45 −/dim c-Kit + KDR − were mobilized. KDR was only expressed by CD19 + B-lymphocytes and CD14 + monocytes subpopulations in circulation. We confirmed by mass cytometry this KDR expression on CD19 + in healthy peripheral and cord blood, also with a VE-cadherin expression, confirming absence of endothelial lineage marker on CD34 + subtypes. In COVID-19, a significant mobilization of CD34 + c-Kit + KDR − cells was observed between moderate and critical COVID-19 patients regardless CD133 or CD45 expression. In order to better evaluate EPC phenotype, we performed imaging flow cytometry measurements of immature CD34 + KDR + cells in cord blood and showed that, after elimination of non-circular events, those cells were all CD19 + . During COVID-19, a significant mobilization of CD19 + KDR + per million of CD45 + cells was observed between moderate and critical COVID-19 patients regardless of CD34 expression. CD34 + c-Kit + cells are mobilized in both cardiovascular disease described here. KDR cells in peripheral blood are CD19 positive cells and are not classic vasculogenic stem and/or progenitor cells. A better evaluation of c-Kit and KDR expressing cells will lead to the redefinition of circulating endothelial progenitors. Graphical abstract Central illustration figure. Multidimensional proteomic approach of endothelial progenitors demonstrate expression of KDR restricted to CD19 cells. Endothelial progenitor cells (EPCs) are involved in cardiovascular diseases, however their phenotype remains elusive. We elucidated here EPCs phenotype by a deep characterization by multidimensional single cell complementary cytometric approaches after Bioprosthetic total artificial heart implantation and during COVID-19. We showed a redistribution of circulating CD34 + and CD19 + sub-populations in both situations. None of the immature cell population expresses KDR. Mobilized CD34 + expressed c-Kit. Imaging flow cytometry demonstrated that CD34 + KDR + cells, after elimination of non-circular events, are all CD19 + . Our results suggest a new definition of circulating EPCs and emphasize involvement of CD19 cells in cardiovascular disease.